Greenhouse gas emissions of the production chain behind consumption of products in Austria: Development and application of a product‐ and technology‐specific approach. (14th November 2019) - Windsperger, Bernhard; Windsperger, Andreas; Bird, David Neil; Schwaiger, Hannes; Jungmeier, Gerfried; Nathani, Carsten; Frischknecht, Rolf
Abstract: Globalization has been one main driver affecting our whole economy. Thus, greenhouse gas emissions (GHGs) associated with imports and exports should get addressed in addition to the national emission inventory according to the United Nations Framework Convention on Climate Change (UNFCCC), which is focused on territorial emissions only. To enable a correct calculation for imports and exports and to find the most emission‐intensive products and their origin, a product‐ and technology‐specific approach would be favorable which has not been applied up to now. This article addresses this research gap in developing and applying such an approach to calculate the GHGs behind consumption of products in Austria. It is based on physical flows combined with life‐cycle‐based emission factors and emission intensities derived from sector‐ and country‐specific energy mix, for calculating all emissions behind the production chain (resources to final products) of products consumed in Austria. The results have shown that consumption of products in Austria leads to about 60% more emissions than those of the national inventory and that the main part of these emissions comes from the provision of products. The most emission‐intensive products are coming from the chemical and the metal industry. In particular, imports are the main driver of these emissions and are more emission intensive than those produced in Austria. As a result, it is necessary to look at practical measures to reduce emissions along the production chain not only in Austria, but especially abroad as well.